"In the Beginning …": A Catholic Understanding of the Story of Creation and the Fall - Bernas, Casimir (Cistercian studies quarterly, 2006)
The article reviews the book "In the Beginning… A Catholic Understanding of the Story of Creation and the Fall," by Joseph Ratzinger.